2020
DOI: 10.1101/2020.11.24.395095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting direct and indirect non-target impacts of biocontrol agents using machine-learning approaches

Abstract: Biological pest control (i.e. ‘biocontrol’) agents can have direct and indirect non-target impacts, and predicting these effects (especially indirect impacts) remains a central challenge in biocontrol risk assessment. The analysis of ecological networks offers a promising approach to understanding the community-wide impacts of biocontrol agents (via direct and indirect interactions). Independently, species traits and phylogenies have been shown to successfully predict species interactions and network structure… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 98 publications
(119 reference statements)
0
2
0
Order By: Relevance
“…Using qualitative food webs, Todd et al (2021) found that showing all known connections between species in a food web diagram could help to reduce uncertainty around which species might be at risk. Kotula et al (2021) tested machine-learning approaches for predicting indirect effects and found that while they were not able to predict indirect effects, they did have potential to rank hosts as having low or high risk of indirect effects. These authors suggested that validation of such predictions post-release would be of value to regulators in future decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Using qualitative food webs, Todd et al (2021) found that showing all known connections between species in a food web diagram could help to reduce uncertainty around which species might be at risk. Kotula et al (2021) tested machine-learning approaches for predicting indirect effects and found that while they were not able to predict indirect effects, they did have potential to rank hosts as having low or high risk of indirect effects. These authors suggested that validation of such predictions post-release would be of value to regulators in future decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, random forest is emerging as a popular method due to its ability to learn nonlinear interactions between predictor variables, outperform other inference methods (Desjardins-Proulx et al 2017, Laigle et al 2018, Sydenham et al 2021, and its availability to a wide range of users-including those without expert programming skills-through several R packages (e.g., Liaw and Wiener 2002, Wright and Ziegler 2017, Seligman 2022. Random forests have been used to predict various interaction types, including plant-pollinator (Ornai andKeasar 2020, Sydenham et al 2021), parasite-host (Kotula et al 2020), and predator-prey interactions (Desjardins-Proulx et al 2017, Parravicini et al 2020. They have also been used to identify which species' traits are most important for predicting whether species interact (Dellinger et al 2019, Klomberg et al 2022.…”
Section: Introductionmentioning
confidence: 99%